Mediatizacija religije in zamikanje religijskih avtoritet - Koren Ošljak, Katja (Poligrafi, 2024)
One of the research objectives of the Recovira international project was to map the online presence of three religious communities in Slovenia: the Roman Catholic Church, the Islamic Community in the Republic of Slovenia, and the Society for Krishna Consciousness. Particular focus was placed on the lockdown period during the epidemic, when most activities of religious communities shifted from sacred buildings to the internet. Since our research interest was exploring the different aspects of digitisation within these communities, we approached data gathering using the netnographic method. The principal objective of the study was to identify the digital or digitised practices of religious communities in relation to religious authority. Against the backdrop of an audience-centred understanding of mediatisation and analysis of digital religious practices during the epidemic, we observed the changes in power relations within the religious communities and re-ached three key conclusions: 1. In the Catholic community, adjustments in daily religious life caused tensions related to participation in religious activities outside churches and the appropriateness of the measures imposed; 2. In the Islamic com-munity, most religious activities were cancelled, and the community was encou-raged to comply with denoted measures; 3. In the Hare Krishna community, by far the most digitally engaged, highly inclusive digitisation practices were promoted and used. Additionally, we identified two cases in which alternative religious authority emerged through digital media.
Keywords: Catholic community; Covid-19; digital ethnography; digitalizacija; digitalna etnografija; Islamic community; islamska skupnost; katoliška skupnost; mediatisation; mediatizacija; netnografija; netnography; Religija; religijska avtoriteta; religion; skupnost za zavest Krišne; Society for Krishna consciousness; Verske skupnosti, sekte ipd.